PANDANGAN MOHAMMAD HATTA MENGENAI DESENTRALISASI DAN KRITIK TERHADAP KLIENTELISME DI INDONESIA - Farid Luthfi Assidiqi; Kushandajani Kushandajani (Mahesa Research Center, 2022)
AbstractThe purpose of this paper is to examine Hatta's thoughts on the urgency of decentralization as well as his criticism of clientelism in Indonesia. This research uses the type of literature study research. The data obtained in this study were analyzed using descriptive discourse analysis methods and critical discourse analysis. The results of this study indicate that Mohammad Hatta prepared for the implementation of decentralization to rely on the autonomy of the Village and District Governments, as well as the implementation of periodic General Elections from the village to the central level. The goal is to organize community participation from the lowest level so that the aspirations of the people can be achieved. This view, both directly, is criticism and suggestion of clientelism that occurs in Indonesia. This practice took place from the beginning of independence until the post-1998 reform era in different ways. Thus, there has been a gap between Hatta's views and hopes for Indonesian democracy with the reality that has occurred in Indonesia's political situation since the beginning of independence until now.